Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik OMI KSU Bukit Maradja Menggunakan metode PROMETHEE - Nanda Fachira Chairani Nst (LPPM STIKOM Tunas Bangsa, 2021)
OMI stands for Mitra Indogrosir Outlet, which is a minimarke network that provides basic necessities and daily necessities.The payment mehtod is buy cash and credit for the employees of the Bukit Maraja sipef. In making labor selection decisions the author uses the PROMETHEE method. Where PROMETHEE is wrong one method of determining the order or priority in MCDM (Multi-Criterion Decision Making). PROMETHEE uses are determine and produce decisions from several alternatives.In it all data are combined into one weight assessment that has been obtained through an assessment of the test result.Decision support systems are not tools decision making;it is a system that helps decision makers by equipping them with information from data that has been processed with relevent and necessary to make decisions about a problem with faster and more about a problem with faster and more accurate. So that thus sytem is not intended to replace decision makers I the process decision making.